The Influence of CAMEL and CSR on Financial Sustainability in Banking Companies Listed on the Indonesia Stock Exchange for the Period 2017-2022 - Agelita, Martika; Rahman, Sulaeman; Kurniawan, Meinanda (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the effect of CAMEL and Corporate Social Responsibility (CSR) on financial sustainability in banking companies listed on the Indonesia Stock Exchange for the period 2017-2022. The research method used is quantitative analysis using secondary data obtained from annual financial reports and sustainability reports of banking companies. CAMEL is a method of assessing bank performance consisting of several important indicators, namely Capital Adequacy Ratio (CAR), Productive Asset Quality (KAP), Net Profit Margin (NPM), Operational Costs, Operational Income (BOPO), Loan to Deposit Ratio (LDR. These indicators are used to measure the financial health and operational efficiency of banks that have an impact on long-term financial sustainability. On the other hand, CSR is a form of corporate social responsibility that is considered to be able to provide a positive impact on the bank's reputation and support the bank's financial sustainability by strengthening the relationship between the bank and stakeholders. Using a quantitative approach, this study processes secondary data that includes information from annual financial reports and sustainability reports to assess the impact of CSR and CAMEL on financial sustainability . The findings of this study are expected to provide important implications for bank management in formulating financial strategies and improving bank social responsibility programs to ensure sustainable growth. The results of this study are also expected to be a reference for banks in strengthening financial performance and creating long-term value fields through the implementation of better CSR practices. In addition, this study provides important implications for stakeholders in understanding the strategic role of SCR and financial performance based on CAMEL in creating financial sustainability of banking companies in Indonesia.